Prewencyjne zachowania prozdrowotne w czasie pandemii COVID-19 młodzieży uczącej się w Polsce w różnych typach szkół średnich - Błaszczyk , Natalia; Koźlarek , Marietta; Grajek Magdalena, Magdalena; Jaskulska , Sylwia (Studia Edukacyjne, 2022)
In the text, we assumed that the type of secondary school students may differentiate preventive health-oriented behaviors during the COVID-19 pandemic. The aim of the text is to analyze the differences and to adopt recommendations for different types of secondary schools. The results of the study on a sample of 746 people aged 14 to 22 show that students of general secondary schools during the COVID-19 pandemic engage in more health prevention behaviors and have a more positive attitude towards them than students from technical secondary schools and from sectoral vocational schools. We design recommendations for educational practice within the framework of the Health Beliefs Model.